Local stakeholders' participation in developing criteria and indicators for sustainable forest management - Pokorny, B.; Prabhu, Ravi; McDougall, C.; Bauch, R. (2004)
Criteria and indicators (C&I) for sustainable forest management are important tools to improve the quality of forest management. In most cases they have been developed by experts, but the participation of stakeholders is essential if the C&I are to be locally relevant and practicable. We asked four stakeholder groups to apply a set of C&I to a forest management unit in the eastern Amazon basin. The study confirmed the importance of involving stakeholders and demonstrated that effective efforts begin with well-defined and clearly understandable C&I. Stakeholders were better able to apply and adapt measurable verifiers than the more indicators and criteria. Intensive communication about personal experiences and subjective interpretations is necessary to prevent misunderstandings and misinterpretations. Our study also confirmed the general practical applicability of C&I and revealed their potential as instruments of communication and learning.